PENGUATAN BUDAYA MUTU MELALUI SUPERVISI PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN BERBASIS NILAI ISLAM - Joko Setiono; Erwin Ardianzah; Ahmad Muhibbin; Anam Sutopo (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to understand the role of educational supervision in strengthening an Islamic values-based quality culture at MI Muhammadiyah Kasihan IV Tegalombo. In the Society 5.0 era, Islamic schools are expected to produce not only intelligent but also moral and civilized students. The study uses a qualitative case study approach. Data were collected through interviews, observations, and documentation involving the principal, teachers, staff, and students. Analysis followed the Miles, Huberman, and Saldana model with source triangulation for validity. The findings reveal that educational supervision is conducted in a humanistic and reflective manner. The principal acts as a murabbi, guiding teachers’ professional and spiritual growth. Quality culture develops from faith-based awareness rather than systemic pressure. The values of sincerity, trustworthiness, excellence (ihsan), and responsibility underpin all educational activities. Supervision is carried out through dialogue and consultation, fostering a spirit of togetherness. Islamic values-based supervision effectively strengthens quality culture, creating a learning ecosystem that is high-quality, character-driven, and spiritually grounded reviving education’s essence as a process of humanization.